Formation characteristics of carbonaceous and nitrogenous disinfection by-products depending on residual organic compounds by CGS and DAF - Maeng, Minsoo; Shahi, Nirmal Kumar; Shin, Gwyam; Son, Heejong; Kwak, Dongheui; Dockko, Seok (Environmental Science and Pollution Research, 2019)
Allogenic organic matter (AOM) composed of extracellular and intracellular organic matter (EOM and IOM) is a major precursor of halogenated carbonaceous and nitrogenous disinfection by-products (C-DBPs and N-DBPs) upon chlorination. The EOM and IOM extracted from Microcystis aeruginosa were analyzed based on bulk parameters and organic fractions with different molecular weight by liquid chromatography with organic carbon detection (LC-OCD). It investigated the efficiency of a conventional gravity system (CGS) and dissolved air flotation (DAF) in the removal of organic precursors, together with measurement of the formation of four major trihalomethanes (THMs) and haloacetonitriles (HANs) in treated water upon chlorination. The results showed that EOM accounted for 59% of building blocks and humic substances, whereas for IOM, 54% were low molecular weight (LMW) neutrals. Both CGS and DAF showed 57–59% removal of dissolved organic carbon (DOC) from EOM and IOM. Regarding DON removal, DAF was found to be more effective, i.e., 8% higher than CGS for EOM. Moreover, the removal of LMW acids and neutrals (not easy to remove and are major precursors of DBPs) from EOM and IOM by DAF was higher than from CGS. The amounts of DBPs measured in all the samples treated for interchlorination were much lower than in the samples for prechlorination. Although the precursors of EOM had a higher concentration than in IOM, THMs and HANs were detected for IOM at a higher concentration, which might be attributed to higher amounts of aromatic, aliphatic moisture and protein compounds in the IOM. Comparatively, DAF showed lower THM and HAN values than CGS water, particularly for IOM. Also, DAF showed a sharp decrease in THMs and an insignificant increase in HANs according to time.
Keywords: Disinfectants; Disinfection; Halogenation; Humic Substances; Microcystis; Nitrogen; Organic Chemicals; Trihalomethanes; Water; Water Pollutants, Chemical; Water Purification; Allogenic organic matter (AOM); Carbonaceous and nitrogenous disinfection by-product (C-DBPs and N-DBPs); Extracellular organic matter (EOM); Intracellular organic matter (IOM); Liquid chromatography with organic carbon detection (LC-OCD)